Work Motivation Of Local Civil Servants In Vietnam (Journal of Namibian Studies : History Politics Culture, 2023)
Work motivation has been shown in various studies to be a factor that motivates civil servants and maintains their efforts in performing public duties. When being motivated to work, civil servants are willing to make efforts, maintain a positive work pace, be proactive and persevere in overcoming difficulties to achieve work productivity. In terms of human resource science, civil servants’ work motivation is defined to consist of objective and subjective influencing factors. In this study, based on a literature review of preceding studies, the theoretical framework of influencing factors to civil servants’ work motivation was built up, addressing justice and accuracy in public service performance appraisal. A survey was conducted to collect opinions of 200 commune – level civil servants from 3 provinces representing 3 regions of Vietnam, including: Hung Yen province (Northern region), Quang Binh province (Central region), An Giang province (Southern region). The results show that justice and accuracy in public service performance appraisal have positive influences on work motivation of Vietnamese civil servants. Of the two factors, "justice in public service performance appraisal" is evaluated at a lower level. The findings lead to recommendations for more appropriate policies to create more work motivation to Vietnamese civil servants.